Rezidivtherapie des Multiplen Myeloms – Individualisierte Konzepte aus dem Arsenal vielfältiger Optionen - Weyermann, Charlotte; Straka, Christian; Einsele, Hermann (DMW - Deutsche Medizinische Wochenschrift, 2020)
The prognosis of patients with multiple myeloma has improved significantly over the past 20 years. However, the patient population in the relapse situation is very heterogeneous due to increasing age and the previous course of the disease and therapy. In particular, the approval of new targeted substances offers numerous treatment options that can be adapted to the individual situation.In relapsed multiple myeloma, disease- and patient-specific factors must be considered for an individually adapted therapy. Suitable patients can also receive an autologous stem cell transplant (ASCT) or, in the case of early relapse after ASCT, an allogenic stem cell transplant, if possible as part clinical studies. Proteasome or immunomodulator-based triple combinations are the standard in recurrence. In frail patients, a combination of two can also be used. The new substances also offer very good therapeutic options for high-risk cytogenetics or renal insufficiency. The monoclonal antibodies Daratumumab and Elotuzumab are well tolerated except for infusion reactions and are highly effective in various combinations, even in high-risk cytogenetics.
Keywords: Rückfall; patientenspezifische Faktoren; Hochrisiko-Zytogenetik; 3-fach-Kombinationen; monoklonale Antikörper